Cyber Patrol and AI-Based Investigations to Disrupt Online Drug Transactions in Indonesia - Ismail, Ismail; Felecia, Felecia; Azizah, Anisa Kurniatul; Rahmawati, Diana (Westscience Press, 2025)
The rise of online drug transactions in Indonesia presents significant challenges for law enforcement due to the anonymity and rapid communication enabled by digital platforms. This study explores the use of cyber patrols and artificial intelligence (AI) in combating these illicit activities, employing a qualitative approach with interviews from four key informants: a cybercrime police officer, a cybersecurity expert, a policy analyst, and an academic. The findings reveal that while cyber patrols serve as an essential tool in identifying and disrupting drug trafficking activities, their effectiveness is often limited by technological and operational constraints. AI emerges as a transformative solution, enabling advanced data analysis and predictive capabilities, though its implementation faces hurdles such as legal ambiguity and resource limitations. The study concludes with actionable recommendations, including increased investment in technology, capacity building, regulatory reforms, and fostering public-private and international collaborations. These strategies are crucial for strengthening Indonesia’s capacity to combat online drug trafficking and ensure a safer digital ecosystem.